2016
DOI: 10.1111/cch.12351
|View full text |Cite
|
Sign up to set email alerts
|

The association between adverse childhood experiences (ACEs) and suicide attempts in a population‐based study

Abstract: Mental health factors and chronic pain appear only to partially mediate relationships between ACEs and lifetime suicide attempts. Future research should look at other pathways with the goal of developing multi-level interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
69
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(75 citation statements)
references
References 40 publications
5
69
1
Order By: Relevance
“…21 The increased odds of suicidality among homeless youth in our study is similar in magnitude to that in population-based samples of adults who experienced multiple ACEs (but not necessarily also homelessness). 22,23 Our study did not assess ACE scores because of limitations of the school-based measures used. Our results imply that family homelessness during childhood and adolescence is itself a potential clinical marker of mental health risk, as reinforced by numerous epidemiologic studies that link residential mobility with adolescent emotional-behavioral problems.…”
Section: Discussionmentioning
confidence: 99%
“…21 The increased odds of suicidality among homeless youth in our study is similar in magnitude to that in population-based samples of adults who experienced multiple ACEs (but not necessarily also homelessness). 22,23 Our study did not assess ACE scores because of limitations of the school-based measures used. Our results imply that family homelessness during childhood and adolescence is itself a potential clinical marker of mental health risk, as reinforced by numerous epidemiologic studies that link residential mobility with adolescent emotional-behavioral problems.…”
Section: Discussionmentioning
confidence: 99%
“…Hughes et al [1] showed that those who have experienced four or more ACEs were around four times more likely to experience adult mental distress. Those who have experienced ACEs have increased rates of psychiatric disorders, including depression, anxiety, Post Traumatic Stress Disorder (PTSD), schizophrenia, substance dependence, self-harm and suicide attempts [5][6][7]. This relationship has been replicated across high, middle and low income countries around the world [8].…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, among adults who experienced physical abuse, rates of suicide ideation were approximately five times higher than among adults without a history of physical abuse (Fuller‐Thomson, Baker, & Brennenstuhl, ). Importantly, these effects have been demonstrated over and above well‐documented suicide risk factors including other adverse childhood experiences as well as adult psychosocial, physical, and mental health factors (Fuller‐Thomson, Baird, Dhrodia, & Brennenstuhl, ), suggesting a unique effect of child maltreatment on the development of risk of suicide ideation.…”
mentioning
confidence: 95%